2020
DOI: 10.1002/jbt.22507
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylases is the major pathway mediated by astaxanthin to antagonize LPS‐induced inflammatory responses in mammary epithelial cells

Abstract: Mastitis is a major inflammatory response of the mammary gland due to various pathogenic invasions and is a serious disease that affects the production yield and health status of cows. Astaxanthin (AST), a xanthophyll carotenoid, is a secondary metabolite synthesized by microalgae and yeasts that has been reported to suppress various inflammatory responses. However, the protective effect of AST on lipopolysaccharide (LPS)‐induced mammary epithelial cells has not yet been reported. The present study results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This result is related to the levels of inflammatory factors secreted by the mammary epithelial cells. According to previous reports, the secretion levels of TNF-α and IL-6 in mammary epithelial cells are significantly lower than in alveolar epithelial cells after treatment with the same concentration of LPS [ 27 , 28 , 29 ]. In addition to the changes in cell morphology, our data showed that LPS increased the expression of Snail.…”
Section: Discussionmentioning
confidence: 92%
“…This result is related to the levels of inflammatory factors secreted by the mammary epithelial cells. According to previous reports, the secretion levels of TNF-α and IL-6 in mammary epithelial cells are significantly lower than in alveolar epithelial cells after treatment with the same concentration of LPS [ 27 , 28 , 29 ]. In addition to the changes in cell morphology, our data showed that LPS increased the expression of Snail.…”
Section: Discussionmentioning
confidence: 92%
“…By increasing IKBα levels through KLF5 and suppressing NF-kB, blocking miR-410 promotes the production of HDAC1 and delays the onset of atherosclerosis. [33] According to Venkidasamy and his team, [34] ATX successfully inhibited the upregulation of HDAC1 expression induced by Lipopolysaccharide (LPS) in mammary epithelial cells. This data may provide evidence that ATX could (ii) RXRA (PDB ID: 6JNO).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports about augmented HDAC activity in endometritis. HDACs are related to the removal of epsilon amino groups from the lysine residue in histones, causing the agglomeration of DNA chromatin ( 50 ). Previous studies have demonstrated that inhibition of HDAC increases histone acetylation, leading to a more open structure of chromatin and promoting DNA transcription ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%